Blockers [videorecording (DVD)] - Mann, Leslie, 1972-; Barinholtz, Ike, 1977-; Cena, John; Buress, Hannibal (Universal Pictures Home Entertainment, 2018)
When three parents discover their daughters' pact to lose their virginity at prom, they launch a covert one-night operation to stop the teens from sealing the deal.